Histological evaluation of the bone repair using mineral trioxide aggregate combined to a material carrier - Falcão-Filho, Hilmo Barreto Leite; Issa, João Paulo Mardegan; Do Nascimento, Cássio; Iyomasa, Mamie Mizusaki; Regalo, Simone Cecílio Hallak; Siéssere, Selma; Pedrazzi, Vinícius; Pitol, Dimitrius Leonardo [UNESP] (My University, 2007)
The aim of this study was to present a possible carrier for MTA, monoolein gel, with the objective to maintain this material in the place that was inserted and verify if this procedure is able to optimize its action. The data were evaluated by histomorphometric method and submitted to statistical analysis. The histological responses observed in this study indicate that the MTA is a reliable material and should be considered effective in bone periapical defects and the monoolein gel was capable to maintain the MTA in situ.
Keywords: Histomorphometry; Monoolein gel; MTA; Periapical defect